Income aspirations and migration: Evidence from rural Tajikistan - Bloem, Jeffrey R.; Lambrecht, Isabel B.; Akramov, Kamiljon T. (SAGE Publications, 2026)
In places with limited employment opportunities, households aspiring to increase their income are mainly left with two options: either (a) invest locally in their farm or non-farm enterprises, or (b) earn income elsewhere via migration. With survey data from 1,705 respondents from rural Tajikistan, we analyze the relationship between income aspirations and household investment strategies, and we contrast this to the relationship between income aspirations and international migration. We find evidence of a strong link between the income aspirations gap and international migration, but, strikingly, we do not observe any association between the income aspirations gap and local investment in farm or non-farm assets. These results suggest that households do not view local investment as a viable strategy for increasing income. Exploring heterogeneity, we find that these results can vary by household poverty status and household land endowments, but not by the respondent's gender. Given the prominence of migration in the study area, this also suggests that remittances commonly serve different purposes than farm or non-farm investments — such as supporting households in their day-to-day expenditures or funding major ritual events.